2014
DOI: 10.1101/lm.036558.114
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of amygdala and cortical NMDA receptors activation upon encoding in odor fear memory

Abstract: Although the basolateral amygdala (BLA) plays a crucial role for the acquisition of fear memories, sensory cortices are involved in their long-term storage in rats. However, the time course of their respective involvement has received little investigation. Here we assessed the role of the glutamatergic N-methyl-D-aspartate (NMDA) receptors in the BLA and olfactory cortex at discrete moments of an odor fear conditioning session. We showed that NMDA receptors in BLA are critically involved in odor fear acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Recent animal work emphasizes an involvement of NMDAR-dependent signalling in medial prefrontal cortex (mPFC) and amygdala during emotional processing and emotion-cognition interactions, including emotional learning (Vieira et al, 2015;Hegoburu et al, 2014;Masneuf et al, 2014). These are in line with studies in humans which revealed emotion-specific disruptions during facial emotion encoding and recognition, as well as altered amygdala and prefrontal functioning following ketamine-induced NMDAR blockade (Ebert et al, 2012;Schmidt et al, 2013, Abel et al, 2003.…”
Section: Introductionsupporting
confidence: 56%
“…Recent animal work emphasizes an involvement of NMDAR-dependent signalling in medial prefrontal cortex (mPFC) and amygdala during emotional processing and emotion-cognition interactions, including emotional learning (Vieira et al, 2015;Hegoburu et al, 2014;Masneuf et al, 2014). These are in line with studies in humans which revealed emotion-specific disruptions during facial emotion encoding and recognition, as well as altered amygdala and prefrontal functioning following ketamine-induced NMDAR blockade (Ebert et al, 2012;Schmidt et al, 2013, Abel et al, 2003.…”
Section: Introductionsupporting
confidence: 56%
“…In accordance with previous studies based on lesion experiments of the lateral EC (Staubli et al 1984;Ferry et al 2006), our results confirmed the observation that the EC is not critical for simple olfactory discrimination. Simple associative olfactory learning has been shown to be mediated by structures such as the olfactory bulb (Gray and Freeman 1986;Gervais et al 1988;Martin et al 2004), the piriform cortex (Litaudon et al 1997;Wilson and Sullivan 2011), and the amygdale (Cousens and Otto 1998;Hegoburu et al 2014). Similarly, we showed that EC inactivation did not impair tactile discrimination and tactile associative learning.…”
Section: Role Of the Dh And The Ec In The Acquisition Of Ot Associationssupporting
confidence: 66%
“…Stressors also alter the expression of GABA ( 27 ) and GABA A receptors in the amygdala ( 28 ). Additionally, glutamate signaling in the amygdala, in particular its N-methyl-D-aspartate (NMDA) receptor, is involved in anxiety-related behavior ( 29 ), and intra-MePD administration of NMDA disrupts ovarian cyclicity in the rat ( 30 ). Whether NMDA or GABA A receptor signaling in the MePD is involved in puberty timing has not been investigated.…”
mentioning
confidence: 99%